The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/10640266.2016.1258940
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of factors related to eating disorder onset in female collegiate athletes and non-athletes

Abstract: Female athletes are at risk for clinical eating disorders, yet their onset experiences have rarely been studied with qualitative methods. This study, which included interviews with 12 collegiate female athletes and 17 non-athletes, identified factors that contributed to eating disorder onset for both subgroups. Inductive content analysis revealed that low self-worth, peer issues, and comorbid psychological disorders were common in both groups. However, athletes reported sport-specific factors including perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 29 publications
4
42
0
7
Order By: Relevance
“…High levels of anxiety mediated the relationships between teammates’ bulimic‐type behaviors and athlete engagement with drive for thinness behaviors and compulsive exercise to prevent negative affect and to control weight. This supports and extends prior cross‐sectional research which has suggested that athletes’ modelling of teammates’ disordered eating is related to increases in their own eating and exercise psychopathology, (Arthur‐Cameselle et al, ; Engel et al, ; Gavrilova et al, ; Scott et al, ). Furthermore, the indirect effect identified suggests that the relationships between modelling of teammates’ bulimic‐type behaviors and subsequent engagement with disordered weight control strategies may be stronger for those with high levels of anxiety.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…High levels of anxiety mediated the relationships between teammates’ bulimic‐type behaviors and athlete engagement with drive for thinness behaviors and compulsive exercise to prevent negative affect and to control weight. This supports and extends prior cross‐sectional research which has suggested that athletes’ modelling of teammates’ disordered eating is related to increases in their own eating and exercise psychopathology, (Arthur‐Cameselle et al, ; Engel et al, ; Gavrilova et al, ; Scott et al, ). Furthermore, the indirect effect identified suggests that the relationships between modelling of teammates’ bulimic‐type behaviors and subsequent engagement with disordered weight control strategies may be stronger for those with high levels of anxiety.…”
Section: Discussionsupporting
confidence: 86%
“…However, teammates may also negatively impact upon athletes eating psychopathology. For example, through the modelling of teammates’ disordered eating (Arthur‐Cameselle, Sossin, & Quatromoni, ; Engel et al, ) or perceiving a pressure from teammates to lose weight/change shape (Petrie, Greenleaf, Carter, & Reel, ; Petrie, Greenleaf, Reel, & Carter, ). In line with this, a large‐scale cross‐sectional study (Scott, Haycraft, & Plateau, ) that assessed the importance of multiple teammate influence mechanisms revealed that for both males and females, the best teammate influence predictors of elevated eating and exercise psychopathology were a perceived pressure from teammates to lose weight/change shape and the modelling of teammates’ bingeing and purging behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tjelesna kompozicija, navike u ishrani i rizici za razvoj poremećaja ishrane u uzorku elitnih sportistkinja. Sportlogia, 14 (1), 63-73. doi:10.5550/sgia.181401.se.pss UVOD Broj žena koje aktivno učestvuju u sportu drastično je porastao u zadnjih nekoliko decenija. Ovaj trend je donio sa sobom brojne fizičke i mentalne koristi sportiskinjama, i generalno uticao na poboljšanje zdravlja fizički aktivnih žena (Mountjoy, Sundgot-Borgen, Burke, Carter, Constantini, Lebrun, Meyer, Sherman, Steffen, Budget i Ljungqvist, 2014).…”
unclassified
“…Tjelesna kompozicija, navike u ishrani i rizici za razvoj poremećaja ishrane u uzorku elitnih sportistkinja. Sportlogia, 14 (1) …”
unclassified